PRODUCT DESIGN SIMPLIFICATION TO INCREASE COMPETITIVENESS WITH A VALUE ENGINEERING APPROACH TO THE WASTAFEL FLEAN INDUSTRY - Ruspendi Ruspendi; Anthon Rudy W; Riki Effendi (Jurnal POLIMESIN, 2021)
The strength of international competitiveness encourages companies to do optimization. Therefore, the increase in productivity which improves competitiveness must be done. The purpose of this study is to look for the best solution to optimize designs with the best value and cheapest engineering approach that can be executed on the sink faucet production. After a value engineering, obtained high-cost items such as components with brass/metal, local and imported material. Then look for alternative designs with cost criteria, namely Life Circle Cost (LCC) and the Initial Cost as well as with zero one non-cost criteria matrix and pairs matrix. The result obtained a design that qualifies for the product by replacing the faucet's construction and dimensions but still meets the requirements of comfort, functionality, and safety in use. With this alternative earned savings of 19.6% of the total cost.